Respiration and circulation - Johnson, Rebecca L.; National Geographic Society (U.S.) (Mumbai Popular Prakashan, 2004)
Overview of the respiratory and circulatory systems, with an explanation of how these systems bring oxygen to the body's cells and carry wastes away. Explores the major parts of each system and describes how scientists are working to find replacements for what fails or wears out.
Originally published by National Geographic under reading expeditions series
Includes bibliographical references (p. 30) and index.
Keywords: Cardiopulmonary system -- Juvenile literature; Cardiovascular system -- Juvenile literature; Lungs -- Juvenile literature; Heart -- Juvenile literature; Blood -- Circulation -- Juvenile literature